Changing faces of Indian women - Bagchi, Anita; Roy, Sanjay K.; University of North Bengal. Centre for Women's Studies; International Seminar on Women's Situations and Women's Studies (2006 : Centre for Women's Studies, North Bengal University) (Kolkata : Levant Books, 2009)
Papers presented at the International Seminar on Women's Situations and Women's Studies, organized by Centre for Women's Studies, North Bengal University, on 18-19 December 2006
Includes bibliographical references and index
Keywords: Women -- India -- Social conditions -- Congresses; Women and religion -- India -- Social conditions -- Congresses; Women in development -- India -- Congresses